Movement for Democratic Change and the Rise of Nelson Chamisa. (March 2021) - Mwonzora, Gift; Hodzi, Obert
Nelson Chamisa is central to the political terrain of contemporary Zimbabwe. Post the soft coup of November 2017 and the death of Morgan Tsvangirai in early 2018, Chamisa became president of the Movement for Democratic Change party and contested the July 2018 presidential election. The tempo of changes in the Movement for Democratic Change presidency is not related directly to the shift from Mugabe to Mnangagwa. However, broader politics formed an important context for Chamisa's contested claim for the Movement for Democratic Change presidency. In examining Chamisa and the Movement for Democratic Change, the article highlights linkages between personality politics and electoral mobilization, and how this relates to political party institutionalization.